Late Presentation of Anal Canal Duplication in Adults: A Series of Four Rare Cases - Mirzaei, Rezvan (Ann Coloproctol, 2015)
Anal canal duplication (ACD) is a very rare condition, especially in adults. Four cases in adults are reported. In three cases, the orifice of duplication was located behind the native anus, and in one case, it was located anteriorly. In all cases, no communication between the anal canal and the tract of duplication was noted. Complete removals of the duplications were done through a perineal approach. Histology showed fibro-muscular tissue lined with a squamous epithelium. The postoperative courses were uneventful.